Waktu Dengung Ruang Sholat Masjid Desa Berdasarkan Perbedaan Bentuk Plafon - Bena, Elsa Fitria; Sudarmo, Beta Suryokusumo; Ridjal, Abraham M. (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2014)
Mosqueâ€™s prayer hall needs optimal reverberation time to get clear sound in the mosque, especially during praying. Praying rites need clear sound . â€œDesaâ€™sâ€ mosques are dominant in quantity in Indonesia. They had many different types. The difference of geometric form affected acoustic performance. In this study, Desaâ€™s mosques would be observed according to their space form: dome, tajug (crown), and flat ceiling. This study would observed six samples of prayer hall, with two samples for each type/form of ceiling: two samples for prayer hall with dome ceiling, two samples for prayer hall with crown ceiling, and two samples for prayer hall with flat ceiling. The result shows that there were no space-ceiling that have optimum reverberation time (RT). All space ceiling type have higher RT than the RT standart. It shows that all the samples perform bad quality of acoustic. According to this research, the best form of ceiling was flat ceiling, while dome ceiling was the worst ones.Keywords: reverberation time, prayer hall of mosque, form of ceiling